Warehouse Inventory System Design in Implementing the CodeIgniter Framework and Scrum Method - Muhammad Yogi Sardi; Uc. Mariance (Journal of Technology Informatics and Engineering, 2024)
When collecting data, sometimes you need tools to make it neater and better at collecting data. The infrastructure section of the Pancabudi Development University which records all incoming and outgoing goods is so large and on a university scale it makes the infrastructure less effective. The research carried out built an Inventory Warehouse System. The research results of the warehouse inventory system that was built were very well used at the Pancabudi Development University in the Facilities and Pre-Means section in warehouse data collection. This system makes it easier for UNPAB Sapras to monitor data on incoming and outgoing goods and can record all types of conditions of goods carried out. The implementation of the Warehouse Inventory System is carried out using data on goods in the UNPAB warehouse. This results in orderly and neat digital data collection. Apart from that, it is more effective because it applies the Scrum method and applies the CodeIgniter framework.